Are Yam Farmers Aware and Willing to Adopt the Aeroponics Farming System in Oyo State, Nigeria? (2021)
Despite the immense returns of new agricultural technologies to increase agricultural productivity and meet rising food demand, there is a lag in the adoption of these technologies by farmers. The aeroponics system is one of such innovative technologies implemented for seed yam propagation. This study assessed the awareness and the determinants of the willingness of yam farmers to adopt the aeroponics farming system, employing the likert scale and the logit regression model. Results showed that more than three-fifths of the farmers had never heard of the aeroponics farming system but were willing to adopt it for yam and seed yam propagation, although high cost of capital required for adoption was a major constraint. Key determinants of farmers' awareness of the aeroponics system include gender, age, education, membership of cooperative society, monthly income and access to extension agent, while the main factors influencing its adoption were marital status, age, access to credit, membership of cooperative society, farm size and income. Efforts at dissemination of aeroponics farming system for increased productivity should be intensified for its effective adoption by the farmers.